Structure of population of Ukraine by phenylthiocarbamide sensitivity - Філіпцова, О. В.; Тимошина, І. А.; Чечуй, О. Ф. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The structure of the sample of population of Ukraine regarding the frequency of phenotypes, genotypes and genes, associated with the phenylthiocarbamide sensitivity, has been studied. It has been shown that in the population there are 22% of those who do not feel the taste of phenylthiocarbamide. Among males, there are a few more non-tasters than among females, however, the differences by the given sample size (n=255) are not statistically significant. The frequency of dominant and recessive allele of the phenylthiocarbamide sensitivity gene calculated on the basis of the Hardy-Weinberg equation amounted in the sample as a whole pT=0.47 and qt=0.53 respectively.